Effect of the stop-signal modality on brain electrical activity associated with suppression of ongoing actions (2019)
To clarify how the modality of stop signals affects the ability to suppress ongoing actions, we compared behavioural indices and event-related potentials (ERPs) recorded in healthy volunteers performing visual and auditory stop-signal tasks. Auditory stop signals were associated with faster reaction times and shorter stop-N2 and stop-P3 latencies. Given that the tasks did not differ in attentional/arousal processes (go-P3 or stop-P3 amplitudes) or motor preparation (LRP amplitude, onset or latency), our results suggest that stop signal modality mainly affects bottom-up sensory processes (faster auditory processing). The ERP waveform obtained by subtracting successfully stopped from unsuccessfully stopped trials showed similar amplitude and topography in both tasks, indicating that the strength of top-down processes related to inhibition was independent of modality. The findings contribute further knowledge about the variables associated with efficient inhibition and have practical implications for the design of settings or interventions to improve reactive inhibition